Building Interpersonal Care Teamwork Skills in a Virtual IPE Simulation Event. Issue 1 (2nd January 2022) - Saldanha, Kennedy; Myler, Linda; Seurynck, Kathleen
ABSTRACT: This is a story about the history and evolution of interprofessional education (IPE) at a mid-sized university in Michigan. It highlights an IPE simulation event conducted virtually during fall 2020, a semester when the university was shut down due to the global pandemic. As the focus of IPE is collaboration between health care and human services teams, primarily in health settings, the care providers and a live patient who suffered a stroke due to COVID-19 and the patient's family were invited to participate in the event. This is a story about interprofessional care, particularly for students preparing to work in teams in health-care settings.